Answer:
Solution point (0,8)
Step-by-step explanation:
Multiply the top equation by 2
- 2*(5x + 3y = 24) Remove the brackets
- 10x + 6y = 48 You could simplify this but don't.
- And multiply the bottom equation by 5
- 5*(-2x - 7y = -56)
- -10x - 35y = -280
Now add the two equations together.
- 10x + 6y = 48
- -10x -35y = - 280 The xs cancel out
- -29y = - 232 Divide by - 29
- y = -232/-29 Do the division
- y = 8
=================
Solve for x
- 5x + 3y = 24 Substitute for y
- 5x + 3*8 = 24 Combine on the left
- 5x + 24 = 24 Subtract 24 from both sides
- 5x = 0 Divide by 5
- x = 0
==================
This one is just a bit messier. I made a graph of it just to show that the answer is correct.